Effective Temperature at Finisher Phase to Promote Relative Growth Rate of Broiler Strain Cobb - Herawati; Adiwinarto, Gatot (International Journal of Poultry Science, 2012)
The objective of this research was to determine the relative growth rate of carcass and their components of Broiler Strain Cobb which were kept at different temperatures. Used 90 male broiler chickens with an average body weight 736.57±39.16 grams. “Split plot” form of the series on home treatment with three different temperatures T1 (34-36°C), T2 (29-32°C) and T3 (20-24°C) was used to analyze the date. The research used RAL basic design, every test was subject to withholding of 3 ages of 28, 35 and 42 days. The parameters studied were the relative growth rate of the chest, thigh, upper thigh, meat and bone. The results showed that the relative growth rate of carcass weight increased and followed with growth of life. At 20-24°C carcass maintenance grew faster (ß>1) from the live weight growth, at all temperatures 34-36°C and 29-32°C carcass growth was equal to the live weight growth (ß=1), relative growth of the chest was similar with the live weight growth, at the temperature of 34-36°C, 29-32°C and 20-24°C, the growth rate of the upper thigh ("thigh") was relative with the live weight growth, which shows the value of ß=1, meaning that growth is equal to the live weight growth, relative growth rate of meat at 20-24°C was more rapid than the growth of carcass (ß>1), but generally at a temperature of 34-36°C, 29-32°C and 20-24°C the growth rate was same as the growth rate of carcass, (can be seen from the value ß=1). The conclusion for the relative growth rate of organs is generally similar to the live weight growth and carcass weight at various temperatures of maintenance. Relative growth rate is faster than the live weight growth at temperature of 20-24°C. Relative growth rate of beef is faster than the live weight growth of carcasses at a temperature of 20-24°C.